Case Report: Development of Type 1 Autoimmune Pancreatitis in an Adolescent With Ulcerative Colitis Mimicking Pancreatic Cancer - Choi, Sujin; Lee, Hae Jeong; Seo, An Na; Bae, Han Ik; Kwon, Hyung Jun; Cho, Chang Min; Lee, So Mi; Choe, Byung-Ho; Kang, Ben (Frontiers in Pediatrics, 2021)
Introduction: Autoimmune pancreatitis (AIP) is a rare extraintestinal manifestation of inflammatory bowel disease (IBD) which is typically responsive to corticosteroid treatment. Case presentation: We report a case of a 17-year-old male diagnosed with ulcerative colitis who subsequently developed acute pancreatitis. Blood tests demonstrated elevated pancreatic enzyme levels of amylase (1319 U/L) and lipase (809 U/L). Abdominal computed tomography revealed peripancreatic fat stranding and the presence of a perisplenic pseudocyst. Azathioprine and mesalazine were stopped as possible causes of drug-induced pancreatitis. However, pancreatic enzymes remained elevated and corticosteroid treatment was started. Despite corticosteroid therapy, amylase and lipase levels continued to increase. Infliximab was started due to a flare in gastrointestinal symptoms of ulcerative colitis. Follow-up abdominal ultrasonography revealed a pancreatic tail mass. Tumor markers, including CA 19-9, were elevated and atypical cells were seen on histological examination of an endoscopic ultrasonography-guided fine needle aspiration biopsy. Surgical pancreaticosplenectomy was performed for suspected pancreatic neoplasm. Surprisingly, histology revealed chronic pancreatitis with storiform fibrosis and infiltration of IgG4-positive cells, compatible with AIP type 1. Thereafter, pancreatic enzymes gradually decreased to normal levels and the patient has been in remission for 9 months on infliximab monotherapy. Conclusion: Pediatric gastroenterologists should keep in mind that AIP may develop during the natural course of pediatric IBD. Moreover, the development of pancreatic fibrosis may be non-responsive to corticosteroid treatment and mimic pancreatic neoplasia.